Photoreforming of glycerol catalyzed by CuO/TiO2 supported on hydroxyapatite - Damrong Adam,; Netnapid Ongsuwan,; Saowapa Chotisuwan, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Waste bovine bones can be used as a source to produce hydroxyapatite (HAp), which is a good organic adsorbent and used as a support material for metal oxide photocatalysts. In this work, HAp powders were prepared from calcination of bovine bones at 900 °C for 2 h and used as supporting material for a TiO2 photocatalyst incorporating CuO. The hexagonal HAp particles were characterized using Fourier transformed infrared spectroscopy (FTIR), X-ray diffraction (XRD), and scanning electron microscopy (SEM). The 50 wt% TiO2 and 1 wt% CuO/TiO2 supported on HAp photocatalysts were synthesized by the co-precipitation method and finally calcined at 450 °C for 4 h. The synthesized HAp and catalysts were characterized by FTIR, XRD, BET surface area analysis, SEM, and transmission electron microscopy (TEM). The photocatalytic performance of the synthesized catalysts was performed by photoreforming of glycerol at room temperature using 100 mL of 0.5 M glycerol solution under nitrogen atmosphere, irradiating with low-light intensity 20 W Mercury UV lamp for 7 h. The gaseous products catalyzed by the synthesized catalysts were analyzed using a gas chromatograph. The maximum hydrogen gas production from photoreforming of glycerol at this condition was obtained at 513.7 µmol gcat –1 without carbon dioxide detection after catalyzing by CuO/TiO2 /HAp catalyst.